Analysis on acceptance level of Malaysian’s consumers towards purchasing the imported rice: case study at Jasin, Melaka / Luqman Hakim Zulkifle and Nabila Huda Aziz - Zulkifle, Luqman Hakim; Aziz, Nabila Huda (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) was the most essential food crop which been cultivated worldwide. It was the second important food crop in the world after wheat and Asia was the largest producer and consumer of rice. In Malaysia, rice was a staple food for Malaysians despite the introduction to other food item. If s production in Malaysia was low as compared with other countries that rice growing in the world. The objective of the study was to determine the factors that influence the acceptance level toward imported rice in Malaysia. Survey method was used for data collection. The questionnaire have been distributed to 200 respondents which 100 males and 100 females. Statistical Package for Science Computer Software (SPSS) were used to analysis result and interpret based on descriptive analysis and factor analysis. Kaiser-Meyer-Olkin Measure oversampling Adequacy (KMO) is 0.766 indicate that the value was acceptable, which means factor analysis was appropriate for the data. Factor analysis result shows that price was the dominant, attribute which represented by four factors that eigenvalues more than 1, factor 1 (willing to buy-imported rice if it is selling at the same price as local rice), factor 2 (buy at wholesale price), factor3 (buy when promotion), factor 4 (willing to buy with government subsidies). It was about 61.42%of the total variance explain by the factors. Therefore, it can be concluded that there was relationship between price and acceptance level of Malaysian's consumers toward purchasing imported rice. As recommendation for future stud}', the improvement and increase the number of independent variables in the stud} to get the real view of factors that can influence consumer’s decision.